The Znt7-null mutation has sex dependent effects on the gut microbiota and goblet cell population in the mouse colon - Mary E. Kable; Niknaz Riazati; Catherine P. Kirschke; Junli Zhao; Surapun Tepaamorndech; Liping Huang; François Blachier (PLoS ONE, 2020)
Cellular homeostasis of zinc, an essential element for living organisms, is tightly regulated by a family of zinc transporters. The zinc transporter 7, ZnT7, is highly expressed on the membrane of the Golgi complex of intestinal epithelial cells and goblet cells. It has previously been shown that Znt7 knockout leads to zinc deficiency and decreased weight gain in C57BL/6 mice on a defined diet. However, effects within the colon are unknown. Given the expression profile of Znt7, we set out to analyze the changes in mucin density and gut microbial composition in the mouse large intestine induced by Znt7 knockout. We fed a semi-purified diet containing 30 mg Zn/kg to Znt7-/- mice with their heterozygous and wild type littermates and found a sex specific effect on colonic mucin density, goblet cell number, and microbiome composition. In male mice Znt7 knockout led to increased goblet cell number and mucin density but had little effect on gut microbiome composition. However, in female mice Znt7 knockout was associated with decreased goblet cell number and mucin density, with increased proportions of the microbial taxa, Allobaculum, relative to wild type. The gut microbial composition was correlated with mucin density in both sexes. These findings suggest that a sex-specific relationship exists between zinc homeostasis, mucin production and the microbial community composition within the colon.